A influência de um jogo de empresas na percepção da necessidade de desenvolvimento de competências em integrantes de empresas familiares - Marcolan, Angela Focking (2009)
This research aims at studying the influences of the business game over the perception of the necessity of managerial skills development by participants of family companies in Santa Maria, (RS). These companies present characteristics that become confusing in the relation among family, business and property. This study adopted a group of methods operacionalized through the development of an activity of university extension that changed the usual research in the administrative sciences, bringing the companies to the university. The theoretical approach in this study is based on three themes: business game, family business and perception. The game applied was the Metaltec Business Game focusing on the qualification of managers of micro and small companies. In order to test the influence of the business game on the process of perception of the necessity of managerial skills development, it was collected a structured group of data in two moments: before and after the application of the game. The population and sample of this study was constituted by 11 participants of family companies, classified in the model of the three circles by de Gersick et al.(1999). The results showed that the business game stimulated the participants to develop their managerial skills. The conclusions indicate that the skillful management contributes to organizations financial benefits, besides providing recommendations for future research.